Structural Characterization of the Acer ukurunduense Chloroplast Genome Relative to Related Species in the Acer Genus - Ren, Weichao; Liu, Chi; Yan, Song; Jiang, Zhehui; Wang, Tianhao; Wang, Zhen; Zhang, Meiqi; Liu, Meiqi; Sun, Jiaying; Gao, Jinhui; Ma, Wei (Frontiers in Genetics, 2022)
Acer ukurunduense refers to a deciduous tree distributed in Northeast Asia, a widely used landscaping tree species. Although several studies have been conducted on the species’ ecological and economic significance, limited information is available on its phylo-genomics. Our study newly constitutes the complete chloroplast (cp) genome of A. ukurunduense into a 156,645 bp circular DNA, which displayed a typical quadripartite structure. In addition, 133 genes were identified, containing 88 protein-coding genes, 37 tRNA genes, and eight rRNA genes. One-hundred-seven simple sequence repeats (SSRs) and 49 repetitive sequences were observed. Thirty-two codons indicated that biased usages were estimated across 20 protein-coding genes (CDS) in A. ukurunduense. Four hotspot regions (trnK-UUU/rps16, ndhF/rpl32, rpl32/trnL-UAG, and ycf1) were detected among the five analyzed Acer species. Those hotspot regions may be useful molecular markers and contribute to future population genetics studies. The phylogenetic analysis demonstrated that A. ukurunduense is most closely associated with the species of Sect. Palmata. A. ukurunduense and A. pubipetiolatum var. pingpienense diverged in 22.11 Mya. We selected one of the hypervariable regions ((trnK-UUU/rps16) to develop a new molecular marker and designed primers, and confirmed that the molecular markers could accurately discriminate five Acer species through Sanger sequencing. By sequencing the cp genome of A. ukurunduense and comparing it with the relative species of Acer, we can effectively address the phylogenetic problems of Acer at the species level and provide insight into future research on population genetics and genetic diversity.